Analisis Analisis Pengaruh Layanan Sirkulasi Terhadap Kepuasan Pemustaka Pada Dinas Perpustakaan Dan Kearsipan Di Kabupaten Bengkayang - Oskar, Oskar Nanda Milen; Hermawan, Anton; Pramoekti Narendra, Albertoes (Pustaka : Jurnal Ilmu-Ilmu Budaya, 2024)
This research aims to assess the influence of circulation services on patron satisfaction at the Bengkayang Library using a quantitative method. This method is considered scientific because it is rational, systematic, measurable, and objective. The study will depict the impact of circulation services on patron satisfaction at the Department of Library and Archives of Bengkayang Regency, employing statistical analysis through the SPSS data processing program version 26. The field study encompasses descriptive statistics involving research data, including an overview of respondents, research variables, measurement tool tests, and classical assumption tests. Ultimately, the research results indicate a positive correlation between circulation services and patron satisfaction. Incremental improvements in circulation services can enhance patron satisfaction at the Bengkayang Library. Questionnaire distribution results show that patrons are satisfied with circulation services, with an average score of 4.00 falling into the "satisfied" category. Recommendations: 1. Enhance the performance of library staff through specialized training to provide optimal service to patrons. 2. Improve circulation service facilities, including reading rooms, cutting-edge technology, and infrastructure such as computers and free Wi-Fi. 3. Add the latest library materials to attract patron interest. 4. Enhance the efficiency of circulation unit services to expedite the book borrowing and return processes. 5. Refine the book borrowing process to ensure smoother transactions without obstacles. By implementing these recommendations, it is expected that the influence of circulation services on patron satisfaction can be enhanced. Increased patron satisfaction will bring benefits to various aspects of circulation services, including facilities, service quality, and more.